MANAGEMENT OF PNEUMONIA WITH MULTILOCULATED LEFT PLEURAL EFFUSION CAUSED BY EXTENDED SPECTRUM BETA-LACTAMASES PRODUCING KLEBSIELLA PNEUMONIAE - Goyal, Suresh (International Journal of Clinical and Biomedical Research, 2015)
Increase in the mortality and morbidity in pleural infection is a concern worldwide due to increasing resistant Gram negative pathogens like Acinetobacter baumannii, Pseudomonas aeruginosa and Klebsiella species. Rise of pneumonia due to K. pneumoniae, is more likely observed in alcoholics, diabetics, hospitalized and patients receiving mechanical ventilation. In the present study, we discuss a case of a 59 year old male patient with pulmonary effusion infected with extended spectrum beta-lactamases (ESBL) producing K. pneumoniae with co-morbidities of uncontrolled Type II diabetes mellitus (DM), hypertension and coronary artery disease (CAD), treated with a newer antibiotic adjuvant entity: Elores (ceftriaxone/sulbactam/disodium edetate) and recovered well. KEYWORDS: Gram negative pathogens; Beta-lactamases; Elores.